2018
DOI: 10.1038/mi.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Novel protective mechanism for interleukin-33 at the mucosal barrier during influenza-associated bacterial superinfection

Abstract: Influenza A is a highly contagious respiratory virus that causes seasonal epidemics and occasional worldwide pandemics. The primary cause of influenza-related mortality is bacterial super-infection. There are numerous mechanisms by which preceding influenza infection attenuates host defense, allowing for increased susceptibility to bacterial pneumonia. Herein, we demonstrate that influenza inhibits Staphylococcus aureus-induced production of IL-33. Restoration of IL-33 during influenza A and MRSA super-infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…We expect that the high levels of type I IFN in the influenza-infected mouse may synergize with our administered IFN-to produce this increase in bacterial burden that we see during superinfection but not bacterial infection alone. Many other cytokines are induced by influenza and play significant roles in its pathogenesis, including type 17 cytokines (23) and IL-1 family members (42). There is likely an interactive role for these players as well in the complex cytokine environment of the influenza-infected lung.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the high levels of type I IFN in the influenza-infected mouse may synergize with our administered IFN-to produce this increase in bacterial burden that we see during superinfection but not bacterial infection alone. Many other cytokines are induced by influenza and play significant roles in its pathogenesis, including type 17 cytokines (23) and IL-1 family members (42). There is likely an interactive role for these players as well in the complex cytokine environment of the influenza-infected lung.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were changes in chemoattractants, we did not see any differences in components of the type 17 immune pathway. This finding is noteworthy because we have previously shown that IL-17 and IL-1 play a role in promoting bacterial clearance during influenza infection (16,22,31). We also investigated components of the type 2 immune pathway and did not measure any differences except for increased gene expression of IL-33 in mice that received FY1 earlier in the course of infection.…”
Section: Discussionmentioning
confidence: 95%
“…We also investigated components of the type 2 immune pathway and did not measure any differences except for increased gene expression of IL-33 in mice that received FY1 earlier in the course of infection. We have previously shown that IL-33 recruits functional phagocytic neutrophils to the lung during postinfluenza MRSA pneumonia and that neutrophil depletion with IL-33 treatment led to increased susceptibility to MRSA pneumonia (22). We suspect that although IL-33 is increased in the mice that received FY1 earlier in the course of influenza infection, it is likely not playing a role in the context of measuring any differences in other type 2 immune pathway cytokines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Considering the relative antimicrobial capacity of each phagocyte subset, neutrophils are likely most important for phagocytic killing of S. aureus in the lung (39,40). Indeed, on a per cell basis, AMs and monocytes in influenza-infected WT lungs contain 10-fold more viable bacteria than neutrophils ( Fig.…”
Section: Discussionmentioning
confidence: 99%